Simplify the expression. \[ \frac{\left(-9 y^{4}\right)^{2}\left(y^{4}\right)^{5}}{9 y}=\square \]
Solución de tutoría real
Responder
Solución
¡Inicia sesión para desbloquear respuestas gratis!
Una plataforma de aprendizaje en la que confían millones de estudiantes y profesores reales.
Revisado y aprobado por el equipo de tutoría de UpStudy
Bonus Knowledge
To simplify the expression \[ \frac{\left(-9 y^{4}\right)^{2}\left(y^{4}\right)^{5}}{9 y}, \] we start with the numerator. First, we simplify \(\left(-9 y^{4}\right)^{2}\): \[ (-9)^{2} = 81 \quad \text{and} \quad (y^{4})^{2} = y^{8} \Rightarrow \left(-9 y^{4}\right)^{2} = 81 y^{8}. \] Next, we simplify \(\left(y^{4}\right)^{5}\): \[ (y^{4})^{5} = y^{20}. \] Now, we can rewrite the numerator: \[ \left(-9 y^{4}\right)^{2} \left(y^{4}\right)^{5} = 81 y^{8} \cdot y^{20} = 81 y^{28}. \] Now, we can substitute back into the original expression: \[ \frac{81 y^{28}}{9 y}. \] Next, we simplify the fraction: \[ \frac{81}{9} = 9 \quad \text{and} \quad \frac{y^{28}}{y} = y^{27}. \] Putting it all together, we have: \[ 9 y^{27}. \] Thus, the simplified expression is: \[ \boxed{9 y^{27}}. \]